Methods and Applications of Multilayer Silk Fibroin Laminates Based on Spatially Controlled Welding in Protein Films. (17th November 2015) - Brenckle, Mark A.; Partlow, Benjamin; Tao, Hu; Applegate, Matthew B.; Reeves, Andrew; Paquette, Mark; Marelli, Benedetto; Kaplan, David L.; Omenetto, Fiorenzo G.
Abstract : Recent use of biopolymers as interface materials between planar, inorganic electronics and biological tissues has required the adaptation of micro‐ and nanofabrication techniques for use with these nontraditional materials. In this work, a method which builds on this principle for spatial control of adhesion in multilayer silk fibroin laminates is investigated. This is accomplished through the addition of a spatially patterned amorphous silk adhesive layer in between the films to be adhered, before thermally processing them with heat (120 °C) and pressure (80 Psi) according to established procedures. A one‐step method for rapid, high‐throughput fabrication is demonstrated, which establishes a strong (1100 kPa) bond between the layers independent of the initial processing conditions of the films. The adhesive layers can be patterned using existing silk fabrication techniques, allowing for the assembly of complex geometries including bilayers and microbubbles. Additionally, the utility of this method is demonstrated for potential applications in drug delivery and transient electronics. This approach provides a versatile method for construction of complex multilayer structures in silk, which with future work may ultimately improve the utility of this material as a bridge between high technology and the biomedical sciences. Abstract : A thermal processing method for producing patterned multilayer laminates in silk fibroin is presented, based on thermal reflow of amorphous protein films. The method is able to produce laminates with strength on the order of the bulk material, and features as small as 100 μm. Applications of geometries produced by this method in bioelectronics and drug delivery are also presented.